Effect of Surface Treatment on Enamel Cracks after Orthodontic Bracket Debonding: Er,Cr:YSGG Laser-Etching versus Acid-Etching - Hassanali Ghaffari; Amirhossein Mirhashemi; Tahereh Baherimoghadam; Amir Azmi; Reza Rasooli (Tehran University of Medical Sciences, 2017)
Objectives: This study sought to compare enamel cracks after orthodontic bracket debonding in the surfaces prepared with erbium, chromium: yttrium-scandium-gallium-garnet (Er,Cr:YSGG) laser and the conventional acid-etching technique. Materials and Methods: This in-vitro experimental study was conducted on 60 sound human premolars extracted for orthodontic purposes. The teeth were randomly divided into two groups (n=30). The teeth in group A were etched with 37% phosphoric acid gel, while the teeth in group B were subjected to Er,Cr:YSGG laser irradiation (gold handpiece, MZ8 tip, 50Hz, 4.5W, 60µs, 80% water and 60% air). Orthodontic brackets were bonded to the enamel surfaces and were then debonded in both groups. The samples were inspected under a stereomicroscope at ×38 magnification to assess the number and length of enamel cracks before bonding and after debonding. Independent-samples t-test was used to compare the frequency of enamel cracks in the two groups. Levene's test was applied to assess the equality of variances. Results: No significant difference was noted in the frequency or length of enamel cracks between the two groups after debonding (P>0.05). Conclusions: Despite the same results of the frequency and length of enamel cracks in the two groups and by considering the side effects of acid-etching (demineralization and formation of white spot lesions), Er,Cr:YSGG laser may be used as an alternative to acid-etching for enamel surface preparation prior to bracket bonding.